A Flap Endonuclease (TcFEN1) Is Involved in Trypanosoma cruzi Cell Proliferation, DNA Repair, and Parasite Survival. Issue 7 (29th December 2016) - Ponce, Ivan; Aldunate, Carmen; Valenzuela, Lucia; Sepúlveda, Sofia; Garrido, Gilda; Kemmerling, Ulrike; Cabrera, Gonzalo; Galanti, Norbel
ABSTRACT: FLAP endonucleases (FEN) are involved both in DNA replication and repair by processing DNA intermediaries presenting a nucleotide flap using its phosphodiesterase activity. In spite of these important functions in DNA metabolism, this enzyme was not yet studied in Trypanosomatids. Trypanosoma cruzi, the ethiological agent of Chagas disease, presents two dividing cellular forms (epimastigote and amastigote) and one non‐proliferative, infective form (trypomastigote). The parasite survives DNA damage produced by reactive species generated in its hosts. The activity of a T. cruzi FLAP endonuclease (TcFEN1) was determined in the three cellular forms of the parasite using a DNA substrate generated by annealing three different oligonucleotides to form a double‐stranded DNA with a 5′ flap in the middle. This activity showed optimal pH and temperature similar to other known FENs. The substrate cut by the flap endonuclease activity could be ligated by the parasite generating a repaired DNA product. A DNA flap endonuclease coding sequence found in the T. cruzi genome (TcFEN1) was cloned, inserted in parasite expression vectors and transfected to epimastigotes. The purified native recombinant protein showed DNA flap endonuclease activity. This endonuclease was found located in the parasite nucleus of transfected epimastigotes and its over‐expression increased both parasite proliferation and survival to H2 O2 . The presence of a flap endonuclease activity in T. cruzi and its nuclear location are indicative of the participation of this enzyme in DNA processing of flap fragments during DNA replication and repair in this parasite of ancient evolutive origin. J. Cell. Biochem. 118: 1722–1732, 2017. © 2016 Wiley Periodicals, Inc. Abstract : FLAP endonucleases (FEN) are involved both in DNA replication and repair. In spite of these important functions this enzyme was not yet studied in Trypanosoma cruzi, the ethiological agent of Chagas disease. Here we show the presence and enzymatic activity of a TcFEN1, that is involved in parasite DNA repair, cell proliferation, and survival.